1996
DOI: 10.1021/ma951812w
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemically-Assisted Modification of Polyethylene Surfaces

Abstract: The oxidation of polyethylene surfaces with a range of mild oxidizing agents enhanced by the use of ultrasound is described. The use of sonochemical methods allows significant levels of surface modification to be achieved using oxidizing agents such as hydrogen peroxide and persulfate salts around ambient temperatures under mild conditions. Changes in the water contact angle and attenuated total reflection IR spectroscopy were used to follow the changes in surface chemistry. Variation of the experimental condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 37 publications
(65 reference statements)
1
28
0
Order By: Relevance
“…The samples were goldsputter coated and observed under different magnifications. This reduction in contact angles obtained is similar to values previously reported for different oxidation techniques [8,9]. However, (0.25, 8, 25) PET presented a larger decrease in water contact angle, from 79.2 to 62.8 , in contrast to 69.3 in the harsh condition (0.25, 8,45).…”
Section: Methodssupporting
confidence: 89%
“…The samples were goldsputter coated and observed under different magnifications. This reduction in contact angles obtained is similar to values previously reported for different oxidation techniques [8,9]. However, (0.25, 8, 25) PET presented a larger decrease in water contact angle, from 79.2 to 62.8 , in contrast to 69.3 in the harsh condition (0.25, 8,45).…”
Section: Methodssupporting
confidence: 89%
“…In principle, LbL assembly can be performed on a wide variety of substrates, including noble metals (e.g., Au, Pt), oxides (e.g., quartz, Si, TiO 2 , mica), and synthetic polymers (e.g., poly(ethylene terephthalate) (PET), poly(methyl methacrylate) (PMMA), polyetherimide). [3,4] In practice, however, formation of well-ordered LbL layers on many polymeric surfaces has proven challenging, [5][6][7] and LbL assembly on hydrophobic polymers such as poly(tetrafluoroethylene) (PTFE), and polyethylene (PE) often requires aggressive ''priming'' methods such as plasma treatments, [5,7] oxidative chemical reactions (piranha/persulfonation), [8,9] or polymeric adsorption. [6,10,11] Our goal is to develop a simple, nondestructive and versatile method that enables LbL assembly to be performed on virtually any substrate (noble metals, semiconductors, metal oxides, synthetic polymers, ceramics, and composites) as a useful addition to the LbL toolbox.…”
mentioning
confidence: 99%
“…20 Previous work employing ultrasound for polymer surface modi®cation includes that by Urban and coworkers 21,22 who found that the rate of base-catalysed dehydrohalogenation of PVF 2 was faster under ultrasound and that lower temperatures could be used, although the depth of modi®cation was less. The current authors have also reported 23,24 that ultrasonic enhancement can allow the oxidation of polyethylene surfaces using relatively mild reagents and so modify its surface composition and properties in a controlled manner.…”
Section: Introductionmentioning
confidence: 74%
“…For more quantitative work, a Sonics and Materials VC600`horn' system was used in the con®guration described previously. 23,25 The sound frequency was 23 kHz and, for the work reported here, a constant intensity of 26.2(AE 1.2) W cm À2 (measured calorimetrically) was used. Thermostatting to approximately AE 0.5°C was achieved by circulating water through a jacket surrounding the reaction vessel.…”
Section: Sonication Proceduresmentioning
confidence: 99%